THE ROLE OF TEACHERS IN STIMULATING EARLY LITERACY DEVELOPMENT IN CHILDREN AGED 5-6 YEARS - Hesti Putri Setianingsih; Fitriana Fitriana (Universitas Tadulako, 2021)
Reading and writing skills are an important part of early childhood education. Early childhood educators must play a role in stimulating these skills, because the challenge for educators is currently faced with the problem of calistung in Kindergarten. Demands are currently emerging from the elementary school level that Kindergarten children after graduating from kindergarten must have these skills. Therefore, there are many studies in developed countries regarding the importance of early literacy in early childhood. Even so, teachers play an important role in stimulating the development of early literacy in children, but in fact the knowledge of teachers about early literacy is very low in many studies. Therefore, this study aims to determine the role that teachers have applied in the development of early literacy for children aged 5-6 years. The results of the questionnaire show that the teacher's role in the development of early literacy for children aged 5-6 years shows a percentage of 63.32%, which is included in the fairly involved category.